2012
DOI: 10.1071/he12183
|View full text |Cite
|
Sign up to set email alerts
|

The implementation of a pilot playground markings project in four Australian primary schools

Abstract: Based on our data, it is unclear whether playground markings are an effective intervention to increase physical activity in the school setting. The amount of playing space available appears to influence the use of the playground markings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…After the exclusion of 207 studies, ten articles composed the descriptive synthesis. 23 , 24 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38
Figure 1 Flowchart of systematic review.
…”
Section: Resultsmentioning
confidence: 99%
“…After the exclusion of 207 studies, ten articles composed the descriptive synthesis. 23 , 24 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38
Figure 1 Flowchart of systematic review.
…”
Section: Resultsmentioning
confidence: 99%
“…This is one of the first studies examining the relationship between playground features and children’s usage and activity levels in public playgrounds using direct observation techniques and audit instruments. Previous studies have all focused particularly on (primary) school playgrounds (Colabianchi et al 2011; Dyment and O’Connell 2013; Kelly et al 2012; Möhrle et al 2015). …”
Section: Discussionmentioning
confidence: 99%
“…15-17, 19-30, 32 Seventeen studies were conducted in the United States,* 12 in Europe (Amsterdam [n = 1], 24 Belgium [n = 2], 16,30 Cypress [n = 1], 23 England [n = 6], 26,38-42 and Scotland [n = 2] 43,44 ), and 3 in Australia. 15,45,46 A majority of the studies (97%) were implemented in samples consisting of boys and girls aged 5 to 13 years. One study was conducted in females only.…”
Section: Resultsmentioning
confidence: 99%
“…16,39 One study employed an intervention that educated children on the benefits of MVPA and taught children active recess games. 27 All intervention studies used one or more objective measures of PA (accelerometers [n = 10], ‡ heart rate monitors [n = 3], 38,39 pedometers [n = 1], 45 SOPLAY [n = 2], 24,25 and CAST 3 [n = 1] 45 ). Three studies reported positive significant findings for PA during recess.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation